Multimedia technologies in university libraries: opportunities and tasks - Tavalbekh Serkhan Ali (Kharkov National Pedagogical University, 2010)
Multimedia technologies (MMT) are considered as a factor of qualitative changes of informational environment of education. Leading role of libraries in the process of integration of MMT environment of university is determined. Influence of libraries experience in usage of informational technologies both traditional and computer-aided, Internet in particular is observed. Determined that introduction of MMT noticeable improving the importance of library in MMT environment organization of universities, improvement of library informational service. Tasks of university libraries with integration into united media space are defining.